1990
DOI: 10.1210/endo-127-1-311
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Ca2+Channels are Involved in Regulation of Steroid Synthesis by Bovine but Not Rat Fasciculata Cells*

Abstract: Bovine but not rat fasciculata cells show a concentration-dependent stimulation of the production of corticosteroids by addition of external Ca2+ to the incubation medium. Both cell types respond to ACTH in a concentration-dependent manner. Increasing concentrations of K+ (0-20 mM) cause increased production of corticosteroids and accelerated influx of Ca2+ in bovine fasciculata cells but no change in either of these two parameters in rat fasciculata cells. Two inhibitors of Ca2+ channels (nifedipine and PY108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 8 publications
4
18
0
Order By: Relevance
“…The identity of the voltage-sensitive Ca 2ϩ channels involved in regulating cortisol secretion has also been controversial. Although low voltage-activated T-type Ca 2ϩ channels are the most prominent channels in nearly all bovine, human, and rat AZF cells, L-type Ca 2ϩ channels are also expressed in at least some of these cells (15,42,60). Confusion regarding the role of L-type Ca 2ϩ channels in the regulation of glucocorticoid secretion by ACTH and ANG II arises from several sources.…”
mentioning
confidence: 99%
“…The identity of the voltage-sensitive Ca 2ϩ channels involved in regulating cortisol secretion has also been controversial. Although low voltage-activated T-type Ca 2ϩ channels are the most prominent channels in nearly all bovine, human, and rat AZF cells, L-type Ca 2ϩ channels are also expressed in at least some of these cells (15,42,60). Confusion regarding the role of L-type Ca 2ϩ channels in the regulation of glucocorticoid secretion by ACTH and ANG II arises from several sources.…”
mentioning
confidence: 99%
“…6). The tested concentration of nifedipine inhibited high K + -induced steroidogenesis completely in isolated bovine adrenocortical cells (Yanagibashi et al 1990).…”
Section: +mentioning
confidence: 90%
“…Our results of the inhibitory effects of these cations on [Ca 2+ ] i mobilization are in agreement with those of Hoth & Penner (1993), and suggest a similar mechanism is involved in BAFC. Yanagibashi et al (1990) showed that the steroidogenic effect of ACTH in the presence of extracellular Ca 2+ was completely abolished by dihydropyridines in freshly isolated bovine adrenocortical cells. They proposed the existence of a VOC which was activated by ACTH in BAFC.…”
Section: Znmentioning
confidence: 98%
See 2 more Smart Citations